Chronic obstructive pulmonary diseases in children - Jose Dirceu Ribeiro; Gilberto Bueno Fischer (Elsevier, 2015)
Objectives: To verify and describe the main events related to the diagnosis and management of chronic obstructive pulmonary diseases in children (COPDC) and adolescents, considering the interrelated physiopathology, genetic, and environmental characteristics. Sources: Relevant literature from PubMed was selected and reviewed. Summary of the findings: COPDC have an environmental and/or genetic origin and its manifestation has manifold genotypes, phenotypes, and endotypes. Although COPDC has no cure, it can be clinically controlled. Chronic cough is the main symptom and bronchiectasis can be present in several COPDC patients. The management of COPDC is more effective if based on guidelines and when treatment regimen adherence is promoted. Oral and inhaled corticosteroids, bronchodilators, inhaled antibiotics, and treatment of pulmonary exacerbation (PE) are the bases of COPDC management, and should be individualized for each patient. Conclusions: Correct diagnosis and knowledge of risk factors and comorbidities are essential in COPDC management. Procedures and drugs used should be based on specific guidelines for each COPDC case. Treatment adherence is critical to obtain the benefits of management. COPDC clinical control must be evaluated by the decrease in PEs, improved quality of life, reduction of pulmonary function loss, and lung structural damage. For most cases of COPDC, monitoring by interdisciplinary teams in specialized reference centers with surveillance strategies and continuous care leads to better outcomes, which must be evaluated by decreasing pulmonary function damage and deterioration, better prognosis, better quality life, and increased life expectancy. Resumo: Objetivos: Verificar e descrever os principais eventos relacionados ao diagnóstico e manejo das doenças pulmonares obstrutivas crônicas em crianças (DPOCC) e adolescentes, tendo em vista a fisiopatologia, características genéticas e ambientais inter-relacionadas. Fonte dos dados: Revisão na base de dado PUBMED com seleção de referências relevantes. Síntese dos dados: As DPOCC têm origem ambiental e/ou genética e se manifestam com diversos genótipos, fenótipos e endótipos e, embora possam ser controladas, não têm cura. O principal sintoma é a tosse crônica e muitas cursam com bronquiectasia. O manejo tem maior eficácia se baseado em guidelines e se a adesão ao regime terapêutico for estimulada e comprovada. Corticóides orais e inalatórios, broncodilatadores, antibióticos inalados e tratamento das exacerbações pulmonares (EP) são vigas mestras do manejo e devem ser individualizados para cada DPOCC. Conclusões: Nas DPOCC é fundamental o diagnóstico correto, conhecer os fatores de risco e comorbidades. Os procedimentos e os medicamentos devem ser baseados em guidelines específicos para cada DPOCC. Adesão ao tratamento é fundamental para obter os benefícios do manejo. O controle deve ser avaliado pela diminuição das EP, melhora na qualidade de vida e redução da evolução da perda da função e dano estrutural pulmonar. Para a maioria das DPOCC, o acompanhamento por equipes interdisciplinares em centros de referência especializados, com estratégias de vigilância e acolhimento contínuos, conduz a melhores desfechos que devem ser avaliados pela diminuição da deterioração do dano e da função pulmonar, melhor prognóstico, melhor qualidade de vida e aumento da expectativa de vida. Keywords: Child, Chronic obstructive pulmonary disease, Chronic cough, Palavras-chave: Criança, Doença pulmonar obstrutiva crônica, Tosse crônica